Exploring the Factor Structure of the Social Cognition and Object Relations–Global Rating Method: Support for Two- and Three-Factor Models. Issue 2 (4th March 2018) - Siefert, Caleb J.; Stein, Michelle; Slavin-Mulford, Jenelle; Haggerty, Greg; Sinclair, Samuel J.; Funke, Danielle; Blais, Mark A.
ABSTRACT: The Social Cognition and Object Relations Scales–Global Rating Method (SCORS–G) contains 8 scales for coding narrative content. This study explores the factor structure of this measure using college ( n = 171), outpatient ( n = 239), and inpatient ( n = 78) samples. Participants told stories to the Thematic Apperception Test (TAT; Murray, 1943) cards. Stories were transcribed and coded by blind raters using the SCORS–G. Cases were randomly assigned to an exploratory or validation group. Exploratory factor analysis with the exploratory group suggested 2- and 3-factor models. The Emotional Investment in Relationships (EIR) scale did not obtain a primary loading on any factor and was not included in subsequentmodels. After modifications, confirmatory factor analysis indicated good-to-adequate fit for 2- and 3-factor models. Both models showed good fit in the validation group and met criteria for invariance across models. Findings indicated that some SCORS–G scales tap cognitive-structural elements, whereas others assess affective-relational components of narratives. We found mild support separating the affective-relational scales in terms of internal representations for the self and others and relationships. The results reported here indicate that clinicians and researchers can calculate a separate cognitive-structural composite score and an affective-relational composite score when using the SCORS–G to rate TAT stories.